Structural 3D Modeling and Creation of a ThreeDimensional Grid - Abdurakhmanova Munisa Mamurjon kizi; Nazirova Elmira Shodmonovna (Zien Journals, 2022)
Structural modeling allows obtaining geometrization of the simulated geological object. The result is a structural model which is also called a structural framework
Keywords: structural; framework; geometrization; geological